What Can Leadership-as-Practice Contribute to OD? - Joseph A. Raelin (Journal of Change Management, 2022)
This paper seeks to find complementarities and make contributions to the field of organization development (OD) from the new field of leadership-as-practice (L-A-P), and in so doing, enhance the development of OD in practice. Rather than looking for leadership in people, especially in their traits and behaviours, leadership-as-practice looks for it in everyday practice, in the spaces between people, and in emergent dynamic social interactions. To find leadership, we look to the practice within which it is occurring. The paper explores these premises by first discussing some of the principal classifications of OD throughout its history. It then offers ways in which L-A-P can potentially enhance OD in both theory and application.
Keywords: M51; M53; M54; 650; organization development; leadership-as-practice; phenomenology